Computational modelling of biomechanics and biotribology in the musculoskeletal system : biomaterials and tissues - Jin, Zhongmin; ScienceDirect eBooks (Cambridge, UK : Woodhead Pub., 2014)
Annotation Modelling is an important aspect of the design process for biomaterials and medical devices. By effectively modelling biomaterials and implants before their implantation, it is now possible to predict certain implant-tissue reactions, degradation and wear. Consequently computational modelling is becoming increasingly important in the design and manufacture of biomedical materials, allowing scientists to more accurately tailor their materials¿ properties for the in vivo environment. The book begins with an introduction to the field and the software and technologies. Part one provides readers with an introduction to the field. Part two covers generic modelling of cells and tissues whilst chapters in part three discuss modelling of biomaterials and interfaces. Part four reviews biomechanics and biotribology with chapters in part five discussing applications of modelling for joint replacements and tissue engineering.
6.4 One-dimensional skeletal muscle modeling6.5 Causes and models of history-dependence of muscle force production; 6.6 Three-dimensional skeletal muscle modeling; 6.7 References; 7 Computational modelling of articular cartilage; 7.1 Introduction; 7.2 Current state in modelling of articular cartilage; 7.3 Comparison and discussion of major theories; 7.4 Applications and challenges; 7.5 Conclusion; 7.6 References; 8 Computational modeling of bone and bone remodeling; 8.1 Introduction; 8.2 Computational modeling examples of bone mechanical properties and bone remodeling.
Online resource; title from title page (Safari, viewed June 23, 2014).
Includes bibliographical references and index.
Safari Books Online
Elsevier
Keywords: Biomechanics; Musculoskeletal system -- Diseases -- Treatment; Biomedical materials; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Biomechanics; Biomedical materials; Musculoskeletal system -- Diseases -- Treatment; Biomechanical Phenomena; Musculoskeletal Physiological Phenomena; Biocompatible Materials; Computer Simulation; Models, Biological; Prostheses and Implants; Electronic books